A DFE coefficient placement algorithm for sparse reverberant channels. - Lopez, M.J.
We develop an automated algorithm for determining the number and sparsely supported locations of coefficients in a multi-element array decision-feedback equalizer based on an estimated channel response. We aim for robustness to a wide variety of possible channel conditions, especially through taking advantage of the interplay between the MMSE-optimal feedforward and feedback filters
Keywords: DFE coefficient placement algorithm; MMSE-optimal feedback filters; MMSE-optimal feedforward filters; Automated algorithm; Channel conditions; Channel response estimation; Multi-element array decision-feedback equalizer; Sparse reverberant channels; Sparsely supported coefficients location; Underwater acoustic channel